Prospects for the Use of Associated Gas of Oil Development as Energy Product - Barkan, Mikhail Shmerovich; Kornev, Anton Vladimirovich (International Journal of Energy Economics and Policy, 2017)
The paper analyzes the scope of associated petroleum gas (APG) losses and estimates the emissions of harmful substances into the atmosphere when associated petroleum gas is burned in flare devices. The technique of industrial monitoring of atmosphere air for industrial facilities of oil development is proposed. The purpose of this work is to create industrial systems for using the resource and energy potential of associated gas of oil development while minimizing a negative impact on the environment under the terms of self-repayment. Keywords: emissions of harmful substances, oil and gas separation, absorption drying, mono-ethanolamine, atmospheric air pollution monitoring. JEL Classifications: Q34, Q43, Q52, Q53